Creative adjustment of linguistic and textual resources in literary translation - Adhikari, Bal Ram (Nepalese Linguistics, 2019)
The present article conceptualizes the process of rewriting the given text in the target language (TL) as regeneration of the text across languages. Shedding light on similarities and differences between producing a text across languages i.e. transwriting and within a language i.e. writing, it is argued that translation is a creative process almost exclusive to linguistic and textual levels.